Enhancing Market Management Systems and Verification Services: Determinants of Vendor Satisfaction in Traditional Vegetable Markets - Putro, Rahadian Kristanto; Kistyanto, Anang; Wardoyo, Dewie Tri Wijayati (Journal of Business Management Education (JBME), 2024)
This research aims to analyze the influence of the market management system and the quality of tera/re-terra services on the satisfaction of traders at the Magetan Regency Vegetable Market. The type of research used was descriptive-quantitative with 80 market traders as respondents obtained through probability sampling techniques. The research results show that the traditional market management system has a positive and significant effect on trader satisfaction. The quality of tera/re-terra service also has a positive influence on trader satisfaction. Simultaneously, the traditional market management system and the quality of tera/reprint services influence trader satisfaction. The implication of this research is the need for market managers to manage market facilities and infrastructure well and add facilities that do not yet exist. Tera/re-terra service officers also need to provide clarity and certainty in serving traders, including regarding tera fees. Future research can explore other variables and conduct studies in other markets and different regions